ORGANIZATION OF THE MODERN EDUCATIONAL ENVIRONMENT OF PRESCHOOL EDUCATION (EARLY CHILDHOOD) - Bondarenko, Natalia; Chornomordenko, Ivan (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2024)
Introduction The state of war poses new challenges for the educational system of Ukraine, in particular for preschool education institutions, which have the maximum possible responsibility for their pupils before parents and society since pupils of preschool education institutions are as much as possible dependent on the guardianship and protection of adults. The aim and tasks. The research aim is to consider the transformations of the modern educational environment of preschool education (early childhood), taking into account modern challenges. Research methods. The methodological basis of the research is a systems approach to study the psychological and educational needs of young children, not only during the martial law in Ukraine but also for further peacetime development. Research results. The main sources of information regarding the adaptation of the educational process to the conditions of martial law are the Ministry of Education and Science of Ukraine and the Institute of Educational Problems National Academy of Pedagogical Sciences of Ukraine. The methodological basis of early education in Ukraine is the "Child" program of the Ministry of Education and Science for children from 2 to 7 years of age. Discussion. However, private early education institutions develop and implement their own early education innovations, such as attention to the development of cause-and-effect relationship in the child’s mind in the educational environment. Conclusions. With high rates of divorce and single motherhood, early childhood education should also be concerned with demonstrating role models, namely healthy male behavior through more male early childhood education workers.